Upaya Meningkatkan Kepekaan Sosial Melalui Layanan Konseling Kelompok Dengan Teknik Modeling pada MTs Al-Ikhwan Banjarmasin - Heiriyah, Ainun; Hayati, Sri Ayatani (Kuras Institute, 2020)
The use of media in providing counseling services greatly affects the skills of counselors in conducting counseling through virtual internet media. The development of communication technology in the era of 4.0 makes counselors more familiar with, utilizing and applying counseling media virtually via the internet. The development of communication technology requires counselors to innovate, especially in providing e-counseling services as a forum for counselors to provide alternative solutions to problems faced by counselees. This research method is descriptive qualitative research, the source of this research data comes from document studies in the form of books and previous research which is used as a source of data that supports research. The results of this study indicate that online counseling is in the form of virtual counseling technology media, namely: websites, telephones or cellphones, email, video conferencing, chat, instant messaging, computers and other social media networks. The ethics that must be considered by online counselors are how to establish good relationships via the internet, confidentiality aspects in the implementation of counseling, legal aspects in telecommunications via the internet and licensing. Thus online counselors are required to work professionally by paying attention to ethics in the implementation of online counseling.